Analisis Nilai-Nilai Pendidikan dalam Seloko Adat Pernikahan Masyarakat Desa Sungai Keruh Kabupaten Tebo - Sari, Ernita; D, Yusra; Ningsih, Arum Gati (Jurnal Ilmiah Dikdaya, 2023)
The problem with this study is the value of what education is found in the murky river village village of tebo district. The purpose of this study is to describe the educational values found in the murky river village village of tebo district. This type of study is a descriptive study using a qualitative approach and is analyzed using the herbal method. The source of this research data is a transcript of the traditional wedding ceremony of the murky river village of tebo district, and the murky rivervillage custom wedding procession between Yuda Anggara bin hamidi and Widia Hepliyani binti Rozali on July 2, 2023, which was then transplanted into script form. The results in this study describe the values of education found in the murdy river village cultures of tebo district, the values of education in which there is (1) the value of the education of faith and education in the almighty god, the value of the education of the almighty god, the value of the natural and inherent belief in god, the value of the supreme deity, (2) the value of the noble moral education includes the virtues of patience, righteousness, and justice, Affection, provident, courageous, ashamed, maintaining chastity, and keeping promises, (3) the value of scientific education includes the value of knowledge and intelligence, (4) the value of democratic education includes the value of human beings having a change in the direction of healthy thought, respect for the dignity of our fellowmen, willingness to serve for common interests or welfare, (5) the value of responsible education includes the value of being accountable to one god, responsibility to oneself, responsibility to the family. It is hoped that studies on the value of education can be continued and that researchers can further examine the values of education found in literature other than taphstrokes, poetry and so on, that research references on educational values will be more available and easier to find.